(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Improving the quality and result in the field of education through the organization of physical science on the basis of Information, modern technalogies and demonstration experiments. Raising interest in science in students. To grow more and more mature specialists working in the field of Science and technology. To generate knowledge and skills ,skills in students by showing their theoretical knowledge on the basis of information technologies and demonstration experiments.